Dual-band independent permittivity sensor using single-port with a pair of U-shaped structures for solid material detection - Alam, Syah; Zakaria, Zahriladha; Surjati, Indra; Shairi, Noor Azwan; Alaydrus, Mudrik; Firmansyah, Teguh (Institute of Electrical and Electronics Engineers Inc., 2022)
This study proposes a single-port dual-band independent microwave sensor for detecting solid materials. The sensor structure consists of a pair U-shaped resonators connected by a power divider and a microstrip feed line with an impedance of 50 Ohms with two different sensing hotspots. The 1st and 2nd resonators operate at a frequency of 1.200 GHz and 2.100 GHz, respectively. The type of material under test (MUT) is a standard material with a size of 10 mm × 10 mm (RO5880, RO4003C, and FR4). The proposed sensor had a very high accuracy compared with both of using permitivitty from datasheet and calibrated frequency from simulation for the 1st and 2nd resonator, respectively. Moreover, the pair of the U-shaped resonators had independent performances and they did not affect each other when the MUT was loaded. Furthermore, it can also operate with single-port measurement, which is a more efficient resource. Finally, the proposed microwave sensor can be a promising solution for detecting different permittivity of solid materials independently with high accuracy for applications such as the food industry, material quality control, and biomedical.